Intracranial Hypertension following Acute Mesenteric Ischemia: A Case Study on the Multiple Compartment Syndrome - Pipolo, Derek O.; Guevara, Sara; Vasiljevic, Lana; Pietrantonio, Andres E. Di; Brennan, Walter; Asmus, Humberto; McCann-Molmenti, Alexia; Cho, Young Min; Shinozaki, Koichiro; Hayashida, Kei; Okuma, Yu; Shoaib, Muhammad; Becker, Lance B.; Decker, Mary E.; Worku, Hermoon A.; Majdak, Petra; Donzelli, Grace; Patel, Akash; Davoud, Sherwin; Vaca-Zorrilla, Andres; Beutler, Sascha S.; Molmenti, Ernesto P.; Miyara, Santiago J. (International Journal of Angiology, 2023)
In this case study, we describe a 25-year-old male who was admitted due to a severe traumatic brain injury, requiring invasive intracranial pressure monitoring. At 48 hours posttrauma, he developed intracranial hypertension refractory to medical treatment without tomographic changes in the brain. Subsequently, intra-abdominal hypertension and tomographic signs of abdominal surgical pathology were observed. An exploratory laparotomy was performed with an intraoperative diagnosis of acute mesenteric ischemia. After surgical intervention for the abdominal pathology, intracranial pressure was restored to physiological values with a favorable recovery of the patient. In this report, the relationship between intracranial pressure and intra-abdominal pressure is discussed, highlighting the delicate association between the brain, abdomen, and thorax. Measures should be taken to avoid increases in intra-abdominal pressure in neurocritical patients. When treating intracranial hypertension refractory to conventional measures, abdominal causes and multiple compartment syndrome must be considered. The cranial compartment has physiological interdependence with other body compartments, where one can be modified by variations from another, giving rise to the concept of multiple compartment syndrome. Understanding this relationship is fundamental for a comprehensive approach of the neurocritical patient. To the best of our knowledge, this is the first report of a comatose patient post-traumatic brain injury, who developed medically unresponsive intracranial hypertension secondary to acute mesenteric ischemia, in which surgical resolution of intra-abdominal pathology resulted in intracranial pressure normalization and restitutio ad integrum of neurological status.
Keywords: intracranial hypertension; acute mesenteric ischemia; multiple compartment syndrome; traumatic brain injury